2021
DOI: 10.1039/d0cc08084e
|View full text |Cite
|
Sign up to set email alerts
|

Boron-modulated surface of hollow nickel framework for improved hydrogen evolution

Abstract: Taking advantage of micro/nano structure engineering and surface boron modulation, we developed a binder-free and support-free electrode to enrich and optimize active sites of Ni.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The pore size distribution at about 3.4 nm ( Figure 2 f) indicated that the sample had good mesoporous properties. In general, an extremely high surface area and abundant pore structure would greatly improve the adsorption site of NiCo 2 O 4 to LiPSs and the infiltration and transfer rate of electrolyte and charge [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pore size distribution at about 3.4 nm ( Figure 2 f) indicated that the sample had good mesoporous properties. In general, an extremely high surface area and abundant pore structure would greatly improve the adsorption site of NiCo 2 O 4 to LiPSs and the infiltration and transfer rate of electrolyte and charge [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al designed and prepared a hollow Ni framework (HNF) with exterior‐interiorly exposed surface active sites, where more efficient Ni–B active sites were introduced in situ on the surface of the HNF by chemical reduction. [ 135 ] As‐synthesized electrode shows excellent HER performance in 1.0 m KOH solution with a small overpotential of 83 mV at 10 mA cm −2 , which even surpasses the commercial Pt/C catalyst at high current density with impressive stability up to 100 h. Electroless plating is a facile method to synthesize binder‐free Ni–B films on conductive electrodes. Wang and co‐workers deposited Ni–B x films on the Cu plate by electroless plating and explored their catalytic HER performance at all pH values.…”
Section: Progresses Of Representative Ni‐based Electrocatalystsmentioning
confidence: 99%
“…6,7 Among transition-metal-based electrocatalysts, Ni and Fe are earth-abundant elements and exhibit high performance in the catalysis of OER, which is beneficial for achieving an optimal interaction strength with OH ad and satisfies the Sabatier principle for catalyst design. [8][9][10] Moreover, it has been proved that Fe can modulate the electronic structure of Ni, which optimizes their adsorption energy and further enhances their electrocatalytic activities. 11 In particular, the special class of NiFe-layered double hydroxide (NiFe LDH) materials are investigated as electrodes for alkaline water splitting.…”
mentioning
confidence: 99%